The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1158/1078-0432.ccr-05-0728
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α–Negative Breast Cancer Tissues Express Significant Levels of Estrogen-Independent Transcription Factors, ERβ1 and ERβ5: Potential Molecular Targets for Chemoprevention

Abstract: We have investigated the expression of two estrogen receptor h (ERh) isoforms, ERh1and ERh5, which activate gene transcription independent of estrogen or growth factors, in ERa-negative breast cancer tissues.We report here, for the first time, that ERa-negative tissues express significant levels of ERh1 and ERh5, and their expression levels are not different from levels in ERapositive tumors. However, significant differences exist between the two racial groups, African American and Caucasian, in that the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 29 publications
0
62
0
Order By: Relevance
“…In our study, nuclear ERh1 expression was not significantly associated with good overall prognosis, nor did we observe any association with tamoxifen sensitivity. Studies of total breast mRNA have shown that ERh5 is the most abundantly expressed isoform in both ERa-positive and ERa-negative cases (32), but the potential contribution of nonepithelial ERh5 expression to these measurements is unknown: We have shown herein that ERh5 is additionally expressed in stromal and endothelial cells and immune infiltrates. The only other protein study on ERh5 in breast cancer was observational and conducted on just 17 cases (33).…”
Section: Discussionmentioning
confidence: 81%
“…In our study, nuclear ERh1 expression was not significantly associated with good overall prognosis, nor did we observe any association with tamoxifen sensitivity. Studies of total breast mRNA have shown that ERh5 is the most abundantly expressed isoform in both ERa-positive and ERa-negative cases (32), but the potential contribution of nonepithelial ERh5 expression to these measurements is unknown: We have shown herein that ERh5 is additionally expressed in stromal and endothelial cells and immune infiltrates. The only other protein study on ERh5 in breast cancer was observational and conducted on just 17 cases (33).…”
Section: Discussionmentioning
confidence: 81%
“…As this was not found when ERb2/cx expression was assessed, it is likely that the correlation with total ERb reflects the ERb1 component, although we cannot exclude the existence of other, as yet unknown variant isoforms. Indeed, the frequent expression of the ERb variant isoform, ERb5, in ERanegative breast tumours has recently been described (Poola et al, 2005), however, we did not have access to specific antibodies to investigate this variant isoform in our breast tumour cohort. Our data confirm and extend an observation made by Jensen et al (2001), where the highest expression of either Ki67 and Cyclin A was found in tumours that only expressed ERb, indicating that ERb may be related to proliferation in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was done randomly blinded to the knowledge on development/nondevelopment of cancer using standard procedures with a single batch of antibody preparation within 1 week on all of the samples. Briefly, slides were deparaffinized and antigens were retrieved in target retrieval solution (Dako) by heating for 25 min in a steamer as previously described (15,43,44) and blocked with 3% H 2 O 2 in methanol for 20 min. The slides were washed with PBS and incubated with avidin block (Vector Laboratories) for 10 min at room temperature followed by washing with PBS and incubating in biotin block (Vector Laboratories) for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%